Analisis Postur Kerja Pekerja Packing Produk Menggunakan Metode RULA di PT. ABC - Faiza, Citra Dian; Herwanto, Dene (Industrika : Jurnal Ilmiah Teknik Industri, 2024)
ABC is a plastic industry company where in the production process the plastic pellets will undergo a molding process which will then form a product. After the production process there are packing workers whose job is to select products that comply with the applicable SOP so that precision is required in sorting the products to be put into packaging. In this case there is a back and forth movement. This can pose a risk to the health of packing workers and will cause complaints of musculoskeletal disorders (MSDS). Therefore, to identify the risk level of body posture of packing workers, work posture measurement methods such as the Rapid Upper Limb Assessment (RULA) method are needed and a questionnaire survey is needed to find out which muscles are at risk using the Nordic Body Map questionnaire. From the results of the survey using the NBM questionnaire, there are several muscle parts that have a high risk of injury, namely the muscles of the lower neck, right shoulder, waist, right ankle with a score of 3 which means pain, as well as the muscles of the back, right and left forearm with a score of 4 which means very ill. Furthermore, the score obtained from measuring work posture using the RULA method is 6, which is at action level 3, which means that packing workers work with a high level of risk, so the work requires inspection and proposed improvements must be implemented. Keywords: Nordic Body Map (NBM), Postur Kerja, Rapid Upper Limb Assessment (RULA).